KONSEP INTERAKSI EDUKATIF DALAM PENDIDIKAN ISLAM (PERSEPTIF AL-QUR’AN) - zulkipli nasution (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2017)
A story in Al Qur‟an is can be related to education if in the interaction of the sory involves the following aspects: the aims of education, educators, learners, materials, and methods. So, the authors in this research, try to examine the stories inside the al-Qur‟an, particularly which of educational interaction model within the people in the past. Thus, from the background above, the research problems of this research were how the concept of educational in Al-Qur‟an perspective and what is the application in education itself is. The primary resources in this research is coming from the story of Ibrahim and Musa (Q.S. Al-Kahfi: 60-82), the story of Ibrahim dan Ismail (Q.S. Al-Shaffat: 102-107), and the story of Luqman (Q.S. Luqman: 12-19). The findings of this research shows that the concept of educational interaction in in the al-Qur‟an consists of 1) the aims of education: humanism, insan kamil, and highest endeavor; 2) the characteristic of educators: wise, mercy, democratic, understanding students‟ psychological condition, knowledgeable, comprehending the materials, patient, and sincere; 3) the characteristics of learners: obedient, determined, patient, strong motivation, never giving up, well mannered, humble, and respecting teachers; 4) Material: aqidah, syari‟ah and akhlak, and 5) methods: dialogic, modelling, democratic, and advicing.